2013
DOI: 10.3126/ajn.v3i0.9008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different mulching materials on weed dynamics and yield of direct seeded rice in Chitwan, Nepal

Abstract: An experiment was carried out at farmers' field to compare the effects of live mulches and herbicide on weed growth and dynamics, yield, and economic performance of direct seeded rice under humid sub-tropical condition at Phulbari, Chitwan in 2009. The experiment was conducted in Randomized Complete Block Design with eight treatments and three replications. The treatments consisted of i) control, ii) three hand weeding, iii) herbicide application (bispyribac sodium @ 80 ml/ha) + one hand weeding, iv) wheat str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 4 publications
3
14
0
Order By: Relevance
“…Long term application of organic amendments were reported to improvement in SOC, available N, P and K in soil, thereby sustaining the soil health (Panwar et al 2010). The use of weed biomass (shrubs) such as Eupatorium adhenophorum as mulching material for soil and moisture conservation and fertility build up in crop production has been also reported by other researchers (Acharya et al 1998 andGaire et al 2013).…”
Section: Soil Fertilitymentioning
confidence: 74%
See 1 more Smart Citation
“…Long term application of organic amendments were reported to improvement in SOC, available N, P and K in soil, thereby sustaining the soil health (Panwar et al 2010). The use of weed biomass (shrubs) such as Eupatorium adhenophorum as mulching material for soil and moisture conservation and fertility build up in crop production has been also reported by other researchers (Acharya et al 1998 andGaire et al 2013).…”
Section: Soil Fertilitymentioning
confidence: 74%
“…The use of biomass from facultative weed such as Eupatorium as mulch has been reported a good source of organic matter *Corresponding author: jayanta.icar@gmail.com and weed suppressor for several upland crops in Himachal Pradesh (Acharya et al 1998). Application of Eupatorium mulch along with HW gave significantly higher yield of upland rice compared to control in Nepal (Gaire et al 2013). A promising way to use allelopathy in weed control is using extracts of alleloopathic plants as natural herbicides (Ankita and Mittal 2012).…”
mentioning
confidence: 99%
“…An experiment was conducted by Shelar (2014) at Dr. Balasaheb Sawant Konkan Krishi Vidyapeeth, Agronomy farm Dapoli during Kharif 2013 to find out effect of methods of sowing and weed control on the performance of direct seeded rice in Konkan region reported that maximum net returns (Rs.16878.66) and B:C ratio (1.37) was recorded in the treatment of pre emergence application of oxadiargyl @ 120 g/ha + post emergence application of bispyribac sodium @ 25 g/ha. Gaire et al (2013) studied the effect of different mulching materials on weed dynamics and yield of direct seeded rice in Chitwan, Nepal and concluded that three hand weeding gave highest gross return, net return and lowest B:C ratio (1.8) as compared to wheat straw mulch (1.9) and lowest B: C ratio (1.5) recorded under weedy check. Mishra and Dash (2013) found that, the pre-emergence application of Oxadiargyl @ 70 g a.i.…”
Section: Economics Of Weed Management Practices In Kharif Ricementioning
confidence: 99%
“…Brown manuring helps smothering weeds, conserving moisture and adding about 15kg N ha -1 without adding much on cost of production (Gaire et al, 2013). A lower broad-leaved weed density and dry weight were observed with Sesbania spp.…”
Section: Effect On Yield Soil Health and Weed Managementmentioning
confidence: 99%